2020
DOI: 10.1063/1.5140030
|View full text |Cite
|
Sign up to set email alerts
|

Optimal architecture for diamond-based wide-field thermal imaging

Abstract: Nitrogen-Vacancy centers in diamond possess an electronic spin resonance that strongly depends on temperature, which makes them efficient temperature sensor with a sensitivity down to a few mK/ √ Hz. However, the high thermal conductivity of the host diamond may strongly damp any temperature variations, leading to invasive measurements when probing local temperature distributions. In view of determining possible and optimal configurations for diamond-based wide-field thermal imaging, we here investigate, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…It is necessary to consider how physical contact of thermometers affect the temperature of the target objects via heat exchange at the interface between the target and the thermometer. This is particularly the case for diamond nanothermometry, which aims to measure the temperature of tiny objects, because diamond has a very high thermal conductivity of 1000-3000 W m −1 K −1 [132] (several times higher than that of copper). Reducing the size of the diamond is necessary to probe the small heat source, whereas the significant size reduction degrades the defect centre properties.…”
Section: Form Of Diamond Sensor: Nanodiamonds and Bulk Diamondsmentioning
confidence: 99%
“…It is necessary to consider how physical contact of thermometers affect the temperature of the target objects via heat exchange at the interface between the target and the thermometer. This is particularly the case for diamond nanothermometry, which aims to measure the temperature of tiny objects, because diamond has a very high thermal conductivity of 1000-3000 W m −1 K −1 [132] (several times higher than that of copper). Reducing the size of the diamond is necessary to probe the small heat source, whereas the significant size reduction degrades the defect centre properties.…”
Section: Form Of Diamond Sensor: Nanodiamonds and Bulk Diamondsmentioning
confidence: 99%
“…The measurement precision was below 0.5 K for all measurements (lower panel in Figure 4B), and an almost uniform temperature distribution (upper panel in Figure 4B) was observed due to the high thermal conductivity of the bulk diamond sample. [37] Based on the static measurement, we further demonstrated the dynamic temperature monitoring, where the temperature is controlled via an electrically-rotated linear polarizer that tunes the heating laser power (red in Figure 4A). By rotating the polarizer at a fixed speed 𝜔, the heating laser power irradiating the sample surface will be tuned in a continuous cosine square pattern (Figure S15A, Supporting Information), indicating a similar pattern in temperature dynamics, i.e., ΔT = A 0 cos 2 (𝜔t + 𝜑) + c. With the event-based OMDR measurement, we achieved a temporal resolution of 0.28 s, demonstrating an easy widefield temperature tracking.…”
Section: Widefield Temperature Dynamics Measurementmentioning
confidence: 99%
“…However, contact thermometers need to consider how they themselves affect the temperature of the target objects via heat exchange at the physical interface between the target and thermometers. This is particularly the case for diamond nanothermometry, which aims to measure the temperature of tiny objects, because diamond has a very high thermal conductivity of 1000-3000 W/(m • K) [124] (several times higher than that of copper). Reducing the size of the diamond is necessary to probe the small heat source, whereas the significant size reduction degrades the defect centre properties.…”
Section: Form Of Diamond Sensor: Nanodiamonds and Bulk Diamondsmentioning
confidence: 99%
“…Nanostructured bulk diamonds have been investigated to introduce bulk-grade diamond quantum thermometry performance to local temperature probing. Tanos et al reported nanopillar structures on bulk diamonds wherein NV centers show excellent spin properties [124]. They analyzed the heat conduction using the finite element method and evaluated the temperature sensing ability of these nanopillar structures.…”
Section: Form Of Diamond Sensor: Nanodiamonds and Bulk Diamondsmentioning
confidence: 99%